Low-frequency conductivity tensor of rat brain tissues inferred from diffusion MRI - Sekino, Masaki; Ohsaki, Hiroyuki; Yamaguchi-Sekino, Sachiko; Iriguchi, Norio; Ueno, Shoogo (Bioelectromagnetics, 2009)
Conductivity tensor maps of the rat brain were obtained using diffusion magnetic resonance imaging (MRI). Signal attenuations in the cortex and the corpus callosum were measured using the stimulated echo acquisition mode (STEAM) sequence with b factors up to 6000 s/mm2. Our previously published method was improved to infer 3 × 3 conductivity tensor at the low‐frequency limit. The conductivity tensor of the tissue was inferred from the fast component of the diffusion tensor and a fraction of the fast component. The mean conductivity (MC) of the cortex and the corpus callosum was 0.52 and 0.62 S/m, respectively. Diffusion‐weighted images were obtained with b factors up to 4500 s/mm2. Conductivity tensor images were calculated from the fast diffusion tensor images. Tissues with highly anisotropic cellular structures, such as the corpus callosum, the internal capsule, and the trigeminal nerve, exhibited high anisotropy in conductivity. The resulting values corresponded to conductivities at the low‐frequency limit because our method assumed electric currents flowing only through extracellular fluid. Bioelectromagnetics 30:489–499, 2009. © 2009 Wiley‐Liss, Inc.